Swirling In

Geometry Level 4

In a triangle A B C ABC , we are given the ratios A F F B = B D D C = C E E A = 17 \dfrac{AF}{FB}=\dfrac{BD}{DC}=\dfrac{CE}{EA}=17 .

If the value of M N N B \dfrac{MN}{NB} can be expressed as p q \dfrac pq , where p p and q q are coprime positive integers, find p + q p + q .

Note: The drawing in not to scale.


The answer is 17.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Marta Reece
Feb 27, 2017

It is generally true that if F B A F = C D D B = A E E C = n \frac{FB}{AF}=\frac{CD}{DB}=\frac{AE}{EC}=n ,then M N N B = n 1 \frac{MN}{NB}=n-1 .

To prove this, I will work with a right triangle. The result will hold true for any triangle derived from it by a linear transformation (that is for any triangle) since linear transformation does not affect ratios of lengths on the same straight line.

Assume A C = A B = n + 1 AC=AB=n+1 . Then equations of the internal lines will be:

y = n x y=nx

y = 1 1 n + 1 x y=1-\frac{1}{n+1}x

y = n + 1 n + 1 n x y=n+1-\frac{n+1}{n}x

The x x -coordinate of M M will come from the intersection of the first two and it will be

x 1 = n + 1 n 2 + n + 1 x_1=\frac{n+1}{n^2+n+1}

The x x -coordinate of N N will come from the intersection of the last two lines and it will be

x 2 = n 2 ( n + 1 ) n 2 + n + 1 x_2=\frac{n^2(n+1)}{n^2+n+1}

The difference between them will need to be divided by the difference between x 2 x_2 and n + 1 n+1 .

( n 2 1 ) ( n + 1 ) n 2 + n + 1 ( n + 1 ) ( n 2 + n + 1 ) n 2 ( n + 1 ) n 2 + n + 1 = ( n 1 ) ( n + 1 ) 2 n 2 + 2 n + 1 = n 1 \frac{\frac{(n^2-1)(n+1)}{n^2+n+1}}{\frac{(n+1)(n^2+n+1)-n^2(n+1)}{n^2+n+1}}=\frac{(n-1)(n+1)^2}{n^2+2n+1}=n-1

The ratio has to be the same for the y y -coordinates and for the lengths themselves, as they all refer to the same straight line and are non-zero.

For n = 17 n=17 the result is 16 = 16 1 16=\frac{16}{1} , so the answer is 16 + 1 = 17 16+1=17 .

There's also a way to use ceva's theorem / menelaus' theorem to get the ratio.

Calvin Lin Staff - 4 years, 3 months ago

Same procedure

Sudhamsh Suraj - 4 years, 3 months ago

Yes Menelaus' theorem is a nice easy way to find this ratio. Further clarify your figure, you new this particular result so you took any figure and put that value 17 17 . If FB / AF = 17 Then FB >>>> AB. That's a mistake, actually when you draw the actual figure instead of solving on that figure you will find that the current answer is w r o n g . wrong.

Vishwash Kumar ΓΞΩ - 4 years, 3 months ago

Log in to reply

Thank you for pointing it out. I have fixed it. It may have happened when some work was done one improving the appearance of the problem. It should be fine now, except that the figure is still not to scale. That part is intentional as the points would be too close together that way.

Marta Reece - 4 years, 3 months ago

What does "The result will hold true for any triangle derived from it by a linear transformation (that is for any triangle) since linear transformation does not affect ratios of lengths on the same straight line." mean ?

What is "linear transformation" ?

Jason Chrysoprase - 4 years, 3 months ago

Log in to reply

Linear transformation can also be found under linear map, for example at https://en.wikipedia.org/wiki/Linear_map

Marta Reece - 4 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...